2001
DOI: 10.1007/s005850000292
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of electron density from incoherent scatter measurements at Arecibo with the IRI-95 model during solar maximum

Abstract: Abstract. Arecibo (18.4 N, 66.7 W) incoherent scatter (IS) observations of electron density N(h) are compared with the International Reference Ionosphere (IRI-95) during midday (10±14 h), for summer, winter and equinox, at solar maximum (1981). The N(h) pro®les below the F2 peak, are normalized to the peak density NmF2 of the F region and are then compared with the IRI-95 model using both the standard B0 (old option) and the Gulyaeva-B0 thickness (new option). The thickness parameter B0 is obtained from the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The CADI‐derived B0 thickness parameter, used in the following analysis, was retrieved using a least squares fit of Relation (1) to the CADI bottomside true height electron density profiles down to 0.24 NmF 2 , or to NmF 1 if an F 1 ‐layer is present, N()h=NmF2exp()xB1cosh()xwhere x = ( hmF 2 − h )/ B 0 [ Sethi and Mahajan , ; Sethi and Pandey , ].…”
Section: Datamentioning
confidence: 99%
“…The CADI‐derived B0 thickness parameter, used in the following analysis, was retrieved using a least squares fit of Relation (1) to the CADI bottomside true height electron density profiles down to 0.24 NmF 2 , or to NmF 1 if an F 1 ‐layer is present, N()h=NmF2exp()xB1cosh()xwhere x = ( hmF 2 − h )/ B 0 [ Sethi and Mahajan , ; Sethi and Pandey , ].…”
Section: Datamentioning
confidence: 99%
“…For B 1, earlier IRI versions [ Bilitza , 1990] took the constant value of 3. Comparisons with observations revealed large discrepancies in the bottomside density at various stations [e.g., Zhang et al , 1996; Sethi and Pandey , 2001, and references therein], therefore there were various attempts to develop a new model for B 0 and B 1 [ Huang and Reinisch , 1997; Adeniyi and Radicella , 1998; Mahajan and Sethi , 2001; Sethi et al , 2000; Zhang et al , 2000] through a series of IRI task force activities [ Radicella , 2001]. Some of the results from these efforts have now been included in the newest IRI model, IRI‐2001.…”
Section: Introductionmentioning
confidence: 99%
“…The overestimation of IRI daytime f o F 2 values found in this work is in good agreement with results of previous studies. For instance, Sethi and Pandey [2000] compared IRI and Arecibo ISR data collected during solar maximum conditions (1981) and found that the values of the electron densities at all heights predicted by IRI (IRI‐95) were larger than those measured by the Arecibo ISR during midday (10–14 LT) for Summer and Equinox periods. Similar results had been found by for solar minimum conditions (1974–1977) using the IRI‐90 model [ Pandey and Sethi , 1996].…”
Section: Resultsmentioning
confidence: 99%
“…In order to model this region, several authors have used the F 2 electron density peak ( N m F 2 ) and the F 2 region peak height ( h m F 2 ) parameters. These parameters depend on various geophysical parameters including local time, season, solar and geomagnetic activity conditions and are believed to describe the overall behavior of the F 2 layer [ Liu et al , 2006; Liu et al , 2003; Zhang and Holt , 2008; Sethi and Pandey , 2000; Moen et al , 2008; Souza et al , 2010; Zhang et al , 2009; Kawamura et al , 2002; Richards , 2001; Lei et al , 2005, and references therein]. A better understanding of the variability and modeling of N m F 2 and h m F 2 parameters is crucial for the development of ionospheric prediction capabilities, improvements in existing ionospheric models, and for radio propagation studies.…”
Section: Introductionmentioning
confidence: 99%